Estrategias de orientación educativa para el desarrollo de habilidades socioemocionales en estudiantes de educación básica media de la escuela “El Vergel”, cantón Valencia - Teran Uriarte, Piedad De Las Mercedes (2025)
The present investigation, aims to analyze the impact of educational guidance on strengthening socio-emotional skills in elementary school students. The project seeks to design pedagogical strategies that promote values such as empathy, emotional self regulation, and conflict resolution, with the goal of improving school coexistence and academic performance. The methodology combines a qualitative and quantitative approach to ensure a comprehensive analysis of the phenomenon under study. Techniques such as direct observation, teacher interviews, and student questionnaires will be employed to